Behavioral Biases Influencing Individual Investors Decision Making in Bearish Trend at Nepse - Pandey Anshu (Journal of Corporate Finance Management and Banking System, 2024)
The discipline of financial economics has seen a paradigm shift over the past 25 years, moving from traditional finance to a new area of the study known as behavioral finance. Due to a multitude of behavioral biases and emotional attachments, professional investors make bad financial decisions that hinder their investing performance. Due to the increase in individual investors over the past several years, which is predicted to continue in the years to come, the problem of behavioral biases may become more and more important. Overconfidence bias, representativeness bias, disposition bias, loss aversion bias, herding bias and market factors are the independent variables, whereas investment decision making is the dependent variable. Questionnaires were used to collect primary data. 200investors were sampled using the convenience sampling technique, and data obtained was subjected to regression analysis. The SPSS was used to analyze data collected in order to generate descriptive statistics for the study. The extent to which the dependent variables could be explained by the independent variable was described using regression analysis. The study thus suggests that individual investors be educated how to avoid poor investment outcomes caused on by behavioral biases. Furthermore, individual investors should seek the advice of stock brokers/fund managers to guide them accordingly in terms of performance of a specific security in which an investor would wish to invest in.